Proceso de atención de enfermería en paciente histerectomizada. - Plúas Bajaña, Zelena Marisol (2022)
Hysterectomy is a surgical intervention based on the extraction or removal of the uterus, however, there has been an increase in the number of cases of hysterectomy in pregnant patients according to data collected indicates that the prevalence, being a public health problem. Hysterectomy is applied as a method of treatment when there are cases of uterine lesions to avoid further complications and in the needs required by the health status of the patient, it is important to note that if they present any abnormality in the uterus and is not treated in time has a high risk of mortality, in the country has shown that in 2 out of 10 women with complications in the uterus untreated have died. In Ecuador the rate of hysterectomies has been determined by the total number of patients aged 15-49 years where only 35.1% have presented these cases, and only 17.5% have received information on risk factors and while 9% have indicated that this process is based on a surgical treatment to avoid fibroids, fibroids and cancer. In this surgical intervention is based on a procedure more employed globally, in much of the clinical cases is evidenced by originating from fibroids and uterine leioma that is dependent on the particular manner of the uterus in general, the process of abdominal surgery is given in partial or total form. The total abdominal hysterectomy may present post-surgery complications in the patient, giving inconveniences for surgeons who must be aware of the process of care and intervention in the patient, in this way it is evident the care of technical principles to avoid as a priority the complications of septicemia to cure the area of surgery with infected elements. Total hysterectomy is a surgical process that consists of extracting or completely removing the uterus, achieving that they can remove the ovaries and fallopian tubes, this process indicates that the patient cannot give way to fertilization, therefore, cannot get pregnant (Carpio & Garnique, 2017, p. 268).